AUGMENTED REALITY BOOK Pengenalan Tata Letak Bangunan dan Landscape Alam Pura Lempuyang - Hanna Cahyani, Agung Ayu; Crisnapati, Padma Nyoman; Gede Sunarya, I Made; Resika Arthana, I Ketut (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
The purpose of this research is to preserve one of Balinese building, Lempuyang Luhur Tempel which is located in Bisbis Hill. In that area, there are landslides and erosion that happened often and risk the temple's holy building. This software is built using augmented reality technology so this software can be one of educational interactive media in learning Lempuyang temple. The narration of this application is made in English so it can also be used as a media to introduce Balinese culture which is known as 'Island of Thousand Temples' in the international community. The research method used in this project is a research and development using waterfall model, there are requirements definition phase (phase of information gathering and system requirement analysis), system and software design (phase of making application design), implementation, and system and software testing. The result of this research is a book that containing information and images related to Pura Lempuyang and an augmented reality application that can be installed on Android smartphones. The images on the book also functioned as a marker for augmented reality applications which capable of displaying objects of Lempuyang Landscape and Lempuyang temple building Layout in 3 dimensional forms. When application displaying 3D objects, this application also equipped with voice narration and explanation in English and music background.